Overlapping Neurological Insults: Case Report of Herpes Zoster in Multibacillary Leprosy with Reversal Reaction - Earlia, Nanda; Pradistha, Aldilla (Heca Sentra Analitika, 2025)
Herpes zoster (HZ) is a reactivation of the varicella zoster virus (VZV). Low immunity, whether due to advanced age, immunosuppressants such as corticosteroids, or chronic infectious conditions such as Morbus Hansen (MH), is the primary predisposing factor for VZV reactivation. A 48-year-old man, previously diagnosed with Morbus Hansen, presented with a painful, burning, erythematous rash that began 5 days before presentation, followed by the development of grouped, fluid-filled blisters on the left waist, some of which ruptured and formed crusts. In the TZANK test, multinucleated giant cells were identified. The patient was given acyclovir, gabapentin, and mupirocin ointment. Leprosy therapy was continued, but corticosteroids were temporarily discontinued until the HZ lesions improved. After 1 week, improvements were observed in the lesions. Adequate therapy is crucial to prevent severe complications in immunocompromised patients. Clinicians should be aware of the potential for this dual disorder, particularly in immunocompromised patients, to promptly identify and manage this condition, thereby minimizing nerve damage, improving patient outcomes, and preventing disability. This case also underscores the need for careful neurological assessment and tailored strategies and therapies in patients with complex infectious neuropathies.